1, 10-Bis(diphenylamino)-4, 6-decadiyne as an active component of a radiochromic film dosimeter. (December 2021) - Soliman, Yasser S.; Abdel-Fattah, Atef A.; Dutremez, Sylvain G.
Abstract: Gamma-irradiation processes are very important tools for minimizing microbial load in dry food, inhibiting the proliferation of T-lymphocytes in blood, and for the sterilization of medical devices. To this end, a composite film dosimeter made of a radiation-sensitive monomer, 1, 10-bis(diphenylamino)-4, 6-decadiyne (DPD), embedded in poly(vinyl alcohol) was prepared using an automatic film applicator system. This polymeric film undergoes a color change from pale yellow to deep orange upon γ-irradiation due to topochemical polymerization of the DPD monomer. This color change is proportional to the amount of absorbed dose. With increasing absorbed doses, gradual disappearance of the νC≡C Raman band of the C≡C-C≡C chemical groups is observed, and new νC≡C and νC = C bands ascribed to the formation of a polydiacetylene with an enyne structure are detected. The irradiated films exhibited two absorption maxima at 470 and 502 nm as measured by UV-Vis spectrophotometry, and the intensities of these bands increased with increasing absorbed doses. Analysis of these films using a high-resolution flatbed scanner (2400 dpi) showed an increase in optical density with increasing absorbed doses up to 269.1 kGy. Stability studies revealed that the irradiated films underwent an increase in the color intensity by ∼3.1% over 50 days of storage. In addition, relative humidities in the range 0–75.3% had a limited impact on the dose response of the films, with a 4% change in this range. The uncertainty (2σ) on dose measurements using the scanner was 4.46%, demonstrating the effectiveness of this film dosimeter for radiation monitoring up to 296.1 kGy. Graphical abstract: Image 1 Highlights: Developing a radiochromic film based on a diacetylene monomer, DPD. DPD polymerizes topochemically by γ-irradiation, causing a color change. Raman spectroscopy shows the formation of poly-DPD chains with increasing doses. Relative humidity (0–75.3%) had a limited impact on the dosimeter response. This film is effective for radiation applications in the 2–269.1 kGy dose range.